Lifestyle and Long-Term Smoking Cessation - Tove Sohlberg; Karin Helmersson Bergmark (SAGE Publishing, 2020)
Background: Since smoking is the leading cause of preventable death, discouraging smoking initiation, encouraging smoking cessation, and exploring factors that help individuals to stay smoke free are immensely important. One such relevant factor may be the impact of lifestyle for long-term smoking cessation. Method: A representative sample of successful quitters was recruited for a study about smoking cessation. These respondents are now part of a 7-year follow-up with the overall aim of revealing factors affecting long-term smoking cessation. Descriptive analyses were carried out at baseline and at follow-up, as well as a further two-step cluster analysis to explore profiles of long-term smoke-free individuals. Results: A majority did not make any particular lifestyle changes, but among those who did, most adopted a healthier lifestyle and/or increased their quota of physical training, where permanent changes in this direction seem to promote a more enduring smoke-free life. Conclusions: Individuals who want to quit smoking should be encouraged to increase their level of physical activity. Swedish health care institutions should be able to provide support for this both initially and over time to promote the long-term maintenance of a smoke-free lifestyle.